1969
DOI: 10.3171/jns.1969.30.2.0172
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Angiography in Identifying False Aneurysm of the Middle Meningeal Artery as a Cause of Extradural Hematoma

Abstract: HERE are 11 cases of posttraumatic false aneurysm of the middle meningeal artery in the world literature. 2,~,7,8,1o,1~2-~4 Six of them were complicated by extradural hematomaY ,~,12,~4 The purpose of this paper is to report one more case causing extradural hematoma and to emphasize the importance of angiography in diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…While most arteriovenous shunts were demonstrated within the first 24 hours after trauma, some were observed after days and even weeks. The longest time interval between trauma and the angiographic demonstration of an arteriovenous shunt in this study was 19 days, which appears to be longer than previously reported in the literature 33,34,50 It is interesting to note that of the various shunt locations the edge location occurs most frequently in the longstanding bleedings. Theoretically, a shorter distance between the bleeding source and the recipient vein as seen in edge shunts would decrease the resistance to flow in the shunt, and contribute to prolong the bleeding in the epidural space.…”
Section: Discussioncontrasting
confidence: 48%
“…While most arteriovenous shunts were demonstrated within the first 24 hours after trauma, some were observed after days and even weeks. The longest time interval between trauma and the angiographic demonstration of an arteriovenous shunt in this study was 19 days, which appears to be longer than previously reported in the literature 33,34,50 It is interesting to note that of the various shunt locations the edge location occurs most frequently in the longstanding bleedings. Theoretically, a shorter distance between the bleeding source and the recipient vein as seen in edge shunts would decrease the resistance to flow in the shunt, and contribute to prolong the bleeding in the epidural space.…”
Section: Discussioncontrasting
confidence: 48%
“…To turn to our case, the false aneurysm developed without any traumatic episode, differing in this respect, from other cases reported (Higazi et al 1969). We think that the dural AVM produced the epidural haematoma spontaneously, and that this haematoma bec~me a false aneurysm, communicating spontaneously with the dural AVM.…”
Section: Discussionmentioning
confidence: 44%
“…On angiography, meningeal pseudoaneurysms have specific characteristics [12, 13]; they are peripherally located at a distance from a branching point and do not show evidence of a neck. The sac is sometimes irregular.…”
Section: Discussionmentioning
confidence: 99%